Fatty Acid Profiles in Managed Care Green and Kemp’s Ridley Turtles over Time - Hayley S. Jones; Larry J. Minter; Craig Harms; Doug Bibus; Liz Koutsos; Kimberly Ange-van Heugten (Journal of Zoological and Botanical Gardens, 2022)
To understand fatty acid status and the potential impact of sample storage, dried blood spot (DBS) samples were collected from fourteen green turtles and ten Kemp’s ridleys undergoing rehabilitation. Half the DBS samples from each animal species were collected in 2021 and sent for immediate analysis while the other half were collected in 2017 from different animals and stored at −80 °C for 4 years before analysis. The blood fatty acid profiles in both species during rehabilitation differed visually from prior wild turtle data. Essential fatty acids linoleic (18:2w6) and linolenic acid (18:3w3) were higher in green turtles than in Kemp’s ridleys but both were approximately half of the percentage previously found in wild turtles. No difference in arachidonic acid between species in rehabilitation were found but percentages were approximately 10% of wild representatives. Sea turtle diets in rehabilitation management may need to be evaluated to ensure species-specific fatty acid balance. Twenty-eight of the 36 individual fatty acids tested were found and all seven fatty acid groupings were detected. When analyzed by storage time, 11 individual fatty acids and four fatty acid groups differed (p = 0.05). When compared by species, 14 individual fatty acids and three groups differed. Current data suggest DBS samples may be best utilized when analyzed immediately.